2014
DOI: 10.1186/s12870-014-0224-4
|View full text |Cite
|
Sign up to set email alerts
|

Early markers are present in both embryogenesis pathways from microspores and immature zygotic embryos in cork oak, Quercus suberL

Abstract: Background: In Quercus suber, cork oak, a Mediterranean forest tree of economic and social interest, rapid production of isogenic lines and clonal propagation of elite genotypes have been achieved by developing in vitro embryogenesis from microspores and zygotic embryos respectively. Despite its high potential in tree breeding strategies, due to their recalcitrancy, the efficiency of embryogenesis in vitro systems in many woody species is still very low since factors responsible for embryogenesis initiation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 45 publications
5
47
0
1
Order By: Relevance
“…In line with this postulate, we observed a significantly decreased level of 5 mC in the embryogenic culture of Arabidopsis and the reduction in the DNA methylation level has also been associated with SE induction in other plants (Santos and Fevereiro 2002;Xu et al 2004;Noceda et al 2009;Rodríguez-Sanz et al 2014;Teyssier et al 2014). However, in some plants, an increased (Fraga et al 2012;Rival et al 2013), differentially modulated (Leljak-Levanić et al 2004;Nic-Can et al 2013) and steady (Parra et al 2001) level of DNA methylation during SE has been reported.…”
Section: Se Induction Is Associated With the Decreased Level Of Globasupporting
confidence: 70%
“…In line with this postulate, we observed a significantly decreased level of 5 mC in the embryogenic culture of Arabidopsis and the reduction in the DNA methylation level has also been associated with SE induction in other plants (Santos and Fevereiro 2002;Xu et al 2004;Noceda et al 2009;Rodríguez-Sanz et al 2014;Teyssier et al 2014). However, in some plants, an increased (Fraga et al 2012;Rival et al 2013), differentially modulated (Leljak-Levanić et al 2004;Nic-Can et al 2013) and steady (Parra et al 2001) level of DNA methylation during SE has been reported.…”
Section: Se Induction Is Associated With the Decreased Level Of Globasupporting
confidence: 70%
“…Besides explant sensitivity, the level of endogenous hormones is one of the critical factors determining the embryogenic potential of the explant (Jiménez 2005). Interestingly, Rodríguez-Sanz et al (2014) reported that an increase of endogenous auxin levels is involved in early in vitro embryogenesis in woody species including the related Q. suber.…”
Section: Discussionmentioning
confidence: 97%
“…At early multicellular embryo cells, a differential and significant increase of IAA endogenous levels was found. After the induction of SE, both explants showed low levels of IAA (Rodríguez-Sanz et al 2014).…”
Section: Auxin Response During the Somatic Embryogenesismentioning
confidence: 98%